FILSAFAT KEAGAMAAN ISLAM DI ANDALUSIA - Nazilatul Laili Sa’adah; Rusma Yulidawati (STIT Darul Hijrah Martapura, 2022)
This manuscript delves into philosophical research that examines philosophy in the context of Islam as a religion, where philosophy is categorized as a discipline that demands deep reflection on tangible objects. The concept of